The effect of sorbed hydrogen on low temperature radial thermal expansion of single-walled carbon nanotube bundles - Dolbin, A.V.; Esel`son, V.B.; Gavrilko, V.G.; Manzhelii, V.G.; Popov, S.N.; Vinnikov, N.A.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The effect of a normal H2 impurity upon the radial thermal expansion ar of single-walled carbon nanotube (SWNT) bundles has been investigated in the interval T = 2.2–27 K using the dilatometric method. It is found that H2 saturation of SWNT bundles causes a shift of the temperature interval of the negative thermal expansion towards lower (as compared to pure carbon nanotubes) temperatures and a sharp increase in the magnitude of ar in the whole range of temperatures investigated. The low temperature desorption of H2 from a powder consisting of bundles of SWNTs, open and closed at the ends, has been investigated.